2014
DOI: 10.2466/26.22.pms.118k11w9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Prior Use of the Same or Different Effectors in a Reaching Action

Abstract: Use of different effectors in two consecutive actions could generate an attentional shift between the effectors with shorter latencies in the second action of reaching. 18 participants (10 men; M age = 21.3 yr.) participated in an experiment with two main variables: (1) effector switching with two levels (Switching and No Switching), where the participants use or do not use a different motor effector for each action; (2) lifting muscles, i.e., the muscles involved in the first phase of the reaching, with two l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…This is also reflected by an increased response time when alternating between different hands in bimanual serial reaction time tasks (Bhakuni and Mutha, 2015;Trapp et al, 2012). Using different limbs within one sequence adds complexity, requiring more coordination and attention to execute the movement sequence according to the movement plan (Gálvez-García et al, 2014). The increased difficulty might inhibit the linking of bimanual sequences (Kennedy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…This is also reflected by an increased response time when alternating between different hands in bimanual serial reaction time tasks (Bhakuni and Mutha, 2015;Trapp et al, 2012). Using different limbs within one sequence adds complexity, requiring more coordination and attention to execute the movement sequence according to the movement plan (Gálvez-García et al, 2014). The increased difficulty might inhibit the linking of bimanual sequences (Kennedy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Fournier et al (2014) showed that when there are several action plans at once, these action plans can interfere with each other to the extent that they share common elements. It is possible that there might be less interference if the tasks did not both involve the index finger of the dominant hand (e.g., see Gálvez-García et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This might be expected if part of the first touch latency included an initial cost the first time any item is touched during a tracking trial (cf. Gálvez-García et al, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…But long intervals near the hands were reproduced for as long as those far from the hands. Attentional switch costs between two responding hands increase as the interval decreases (Gálvez-García, Gabaude, De la Rosa, & Gomez, 2014;Gálvez-García, Peña, Albayay, & Cohen, 2018;Garner, Tombu, & Dux, 2014), thus attentional switch between two responding hands influences temporal reproduction for a short interval more than for a long interval. In addition, previous studies showed differences between one-hand and two-hand configurations (Bush & Vecera, 2014).…”
Section: Methodsmentioning
confidence: 99%